Phantoms, failure and the future: a curatorial residency at the Johannesburg Art Gallery - Hart, Gemma (My University, 2020)
The Johannesburg Art Gallery has operated as the central site and encapsulated experimentation for three emerging curators. The aim of this paper is primarily to identify and cultivate opportunities for emerging practitioners. This has been facilitated through an exploration of how developing fluid platforms can be used to think through alternate ways of practicing in the arts and how this can be imagined into the seemingly rigid structures of existing institutions. This project has taken the form of a part-residency, part-lab and part-workshop, as a means to explore the museum as a pedagogical platform. The interdisciplinary project has served as a platform to apply the theoretical foundations regarding archival, curatorial and exhibition practice to actively investigate the historically haunting held paradigms of museum space through a sensory learning process. By piloting close collaboration between individuals and the institution this project has attempted to bridge the gap between theory and practice through the generation of knowledge production. The skills acquired by the practitioners articulate a dynamic of knowledge-sharing. The residency has been structured through a series of workshops including film screenings, reading groups and archive exploration as a means to conceptually situate themselves within the institution. A conceptual link between the institution, participants and the project itself is situated around the notion of transitional space and the precariousness that comes with it. The precariousness of changing museum structures in a continual search for relevance. The precariousness of young practitioners transitioning between the academy and professional practice. The precariousness of funding for experimental projects. The precariousness of navigating interpersonal relationships within collaboration. All of these elements and countless others account for a near-perpetual state of uncertainty. Therefore, the approach taken has aimed to work with, rather than against limitations. This research considers the function of failure as a creative catalyst - maintaining flexibility and fluidity within the rigid structures of the institution. Central to this thinking is a consideration of how curatorial practice can facilitate integration and enrich the larger art ecology
A research report submitted in partial fulfilment of a Masters Degree in Contemporary Curatorial Practices at the University of the Witwatersrand, Wits School of Arts, 2020